Ceutorhynchus leprieuri Brisout und Ceutorhynchus sulcicollis Paykull (Coleoptera: Curculionidae). - Hayn, Wilhelm (Contributions to Entomology = Beiträge zur Entomologie, 1970)
Distribution, morphology, habits and development of Ceutorhynchus leprieuri Brisout and Ceutorhynchus sulcicollis Paykull are described, and findings about oviposition, embryonal and larval development and pupation are reported. Both weevils populate winter cultures of Brassica in autumn. The determination of the Central European types of Ceutorhynchus leprieuri Brisout is clarified. It was found that its galls on Brassica napus L. and B. rapa L. can have various forms, which differs from previous observations. A number of disparities in previous publications on Ceutorhynchus sulcicollis Paykull is pointed out. In spring the oviposition of the weevil and the habits of the larvae can cause of confusion with C. quadridens Panzer. A differentiating diagnosis is given.